INVESTIGATING THE IMPLEMENTATION OF TEACHING METHODS IN WRITING AND LISTENING AT SINGARAJA MONTESSORI SCHOOL - Klose, Yesaya Yuda; Kurniansyah, Pasya Rafi; Santosa, Made Hery; Rewa, Gde Arys Bayu (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2025)
This study investigates the implementation of writing and listening teaching methods at Singaraja Montessori School with a focus on their effectiveness in cultivating students' independence, character development, and adaptation to individual needs. The research used a qualitative descriptive observational method involving 20 students from grades 4 to 6, with data collected through structured observations and semi-structured interviews with teachers. The findings of the study emphasize the development of students' independence, where students engage in self-directed learning activities that enhance problem-solving abilities. In addition, character development is prioritized through collaborative projects that instill empathy and cooperation. Other findings spotlight the challenges in realizing Montessori principles due to limited resources for continuous teacher training. Holistically, this study concludes that the Montessori approach at Singaraja School shows hope in educating independent and socially responsible students. Hence, the research can contribute positively to enhance the teaching practices of Montessori teachers in various educational contexts.